Comprehensive Detection of Candidate Pathogens in the Lower Respiratory Tract of Pediatric Patients With Unexpected Cardiopulmonary Deterioration Using Next-Generation Sequencing. Issue 11 (November 2020) - Takeuchi, Suguru; Kawada, Jun-ichi; Horiba, Kazuhiro; Yamaguchi, Makoto; Okumura, Toshihiko; Suzuki, Takako; Torii, Yuka; Kawabe, Shinji; Wada, Sho; Ikeyama, Takanari; Ito, Yoshinori
Abstract : Objectives: Next-generation sequencing has been applied to the investigation of microorganisms in several clinical settings. We investigated the infectious etiologies in respiratory specimens from pediatric patients with unexpected cardiopulmonary deterioration using next-generation sequencing. Design: Retrospective, single-center, observational study. Setting: Tertiary care, a children's hospital. Subjects: The study enrolled a total of 16 pediatric patients with unexpected cardiopulmonary deterioration who were admitted to the PICU. Ten bronchoalveolar lavage fluid and six transtracheal aspirate samples were analyzed. Interventions: None. Measurements and Main Results: RNA libraries were prepared from specimens and analyzed using next-generation sequencing. One or more bacterial/viral pathogens were detected in the bronchoalveolar lavage fluid or transtracheal aspirate specimens from 10 patients. Bacterial and viral coinfection was considered in four cases. Compared with the conventional culture and viral antigen test results, an additional six bacterial and four viral pathogens were identified by next-generation sequencing. Conversely, among 18 pathogens identified by the conventional methods, nine pathogens were detected by next-generation sequencing. Candidate pathogens (e.g., coxsackievirus A6 and Chlamydia trachomatis ) were detected by next-generation sequencing in four of 10 patients in whom no causative pathogen had been identified by conventional methods. Conclusions: Our results suggest that viral and bacterial infections are common triggers in unexpected cardiopulmonary deterioration in pediatric patients. Next-generation sequencing has the potential to contribute to clarification of the etiology of pediatric critical illness. Abstract : Supplemental Digital Content is available in the text.